Learning from accidents: Nontechnical skills deficiency in the European process industry - Tusher, H.M. (John Wiley and Sons Inc, 2022)
Safety-critical industries have long been subjected to extensive research and development to enhance operator performance to improve their efficiency. From a human factors perspective, much of the work in process industries is related to either enhancing technical training of operators or related to improving the physical ergonomics of hazardous workplaces. The importance of Nontechnical Skills (NTS) in the process industries have traditionally been less emphasized, while other domains (e.g., aviation, healthcare) have led the development of investigating and improving NTS for the sharp-end operators. This study aims to investigate the association of NTS deficiencies to the major accidents from the past 5 years in the process industries within the European Union by analyzing the accident reports from The Major Accident Reporting System (MARS) database. The accident analysis results reveal potential NTS deficiencies in 27 (17 out of 64) of the cases involving the lack of situational awareness, decision making, problem-solving, communication, leadership, and time management issues. Based on the results of the analysis, a few implications, as well as future research directions, are proposed, which could facilitate the stakeholders in addressing NTS deficiencies of European process industry operators. Â© 2022 The Authors. Process Safety Progress published by Wiley Periodicals LLC on behalf of American Institute of Chemical Engineers.